Personal Factors Underlying Resilience in Adolescence: Cross-Cultural Validity of the Prince-Embury Model. (25th September 2017) - Villasana, Mercedes; Alonso-Tapia, Jesús; Ruiz, Miguel A.
Abstract: Resiliency personality factors are supposed to underlie resilience. To get evidence on this supposition, the Prince-Embury scales (PES) for adolescents were adapted to the Spanish population. Then, the relationship between the resiliency variables sense of mastery, sense of relatedness and emotional reactivity -assessed with the PES- with resilience -assessed with the Subjective Resilience Questionnaire (SRQ)- were analyzed, as well as the role of social integration within this relationship. Data from 1083 adolescents were analyzed using confirmatory techniques (CFA, PALV). CFA of PES displayed a good fit to the model (CFI: .95). Path-analysis showed that sense of mastery and emotional reactivity predict resilience as expected, but also that, contrary to expectations based on Prince-Embury's theory, sense of relatedness and resilience are not related, either directly, or through social integration. Being related and socially integrated probably favors well-being, but it may not favor resilience unless associated to Sense of Mastery, at least in adolescence.